Fostering innovation through stakeholders' engagement at the healthcare industry: Tapping the right key. Issue 8 (August 2020) - Segarra-Oña, Marival; Peiró-Signes, Ángel; Verma, Rohit
Highlights: Innovation outputs can be enhanced by strengthening relationships with its stakeholders. Our model puts together stakeholders' engagement, innovation objectives and innovation outputs. Strong methodology with data from 400+ healthcare Spanish companies using PLS modelling. Stakeholders' engagement is directly and positively related to innovation outputs. Abstract: In this paper we investigate to which point each of the healthcare industry's stakeholders are influencing the final innovation outputs. We propose and test a model that puts together stakeholders' engagement, innovation objectives and innovation outputs. We analyze data from 400+ healthcare Spanish companies using Partial Least Squared modelling technique. Results show that stakeholders' engagement is crucial to orientate innovation objectives that are directly and positively related to innovation outputs. Also, results push to a higher implication of society in the co-creation and participation in innovation activities in the healthcare industry highlighting its importance as, both, triggers and the most benefited recipients. This paper uncovers the relationship among healthcare stakeholders and innovation outputs and also answers another research question—which stakeholders have a stronger relationship with innovation outputs. Implications suggest that healthcare industry managers and policy makers should build on the relationship with clients/customers/patients/final users as innovation-related information inputs as an effective way to improve their innovation outputs.